Innovation in Public Health Education through Student Service Programme - Muhammad Yunus; Fatria Ulfa Wibowo, Fayza Norfazriani A, Hari Juanda, Heru Dwi Frandika, Hilma Rizqina, M. Yazidane (UMBanjarmasin, 2024)
This article discusses a community service programme in Tungkaran Village that focused on health education to prevent stunting. The programme included activities such as educating the community about stunting, providing nutrition counselling, offering health facilities, and promoting clean and healthy living. The programme resulted in increased knowledge and awareness about stunting prevention, the adoption of healthy habits, and improved access to health services. The active participation of the community, along with support from the village government and local health workers, played a key role in the programme's success. The outcomes of this programme are expected to have a lasting impact on the health and well-being of the Tungkaran Village community and can serve as a model for similar initiatives in other areas.